PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING MELALUI MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 1 BRONDONG TAHUN PELAJARAN 2017/2018 - Mariana Wasti Enggelina Banu; Lilik Mawartiningsih (BIO-PEDAGOGI, 2018)
Education is the most important in human life especially with the development of science and technology as a supporter in education. The main problem faced by the world of education is the low level of student learning outcomes. Based on the results of field observations obtained data, that the average score achieved in grade VIII students less than KKM. So need to do research by using blended learning model. This study aims to determine the effect of blended learning model of learning outcomes of students of SMP Negeri I Brondong academic year 2017/2018. This research belongs to Quasi experimental research by using pretest-post test. The instruments used in this study are pretest and posttest test. The data obtained from this research is then analyzed using t-test. Based on the results of research on the effect of learning model of blended learning through the media of image on the students of class VIII SMPN I Brondong Lamongan Year 2017/2018 that is the influence of learning model blended learning through the media images of student learning outcomes on the subject of excretory system. The result of the research shows that there are significant differences in the results of the class biology study which are studied using the conventional model and the class that is taught using the blended learning model through the media of the picture in the VIII students of SMP Negeri I Brondong. The result of data analysis of student learning result showed that the average value of cognitive domain of experimental class is 76.2 while control class is 72,4%. From the analysis of data can be concluded the average value of the experimental class is higher than the control class. It is there influence the learning model blended learning through the media images of student learning outcomes.